Translation Strategies of English Idiomatic Expression in The Shawshank Redemption Movie Subtitle - Difatrialdi Muji Pangestu; Mahyuni Mahyuni; Sudirman Wilian (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2022)
The Shawshank Redemption movie is a meaningful movie which needs to knows more about. The objective of this research is to examine the translation strategy of idiomatic expressions used by the translator in The Shawshank Redemption movie subtitle. The data is obtained by watching closely The Shawshank Redemption movie repeatedly, note-taking, compare the idiomatic expression used by the characters and its translation strategies in the subtitle from the movie. The data that has been collected is translates using Baker’s Theory but descriptively outlined. The result of this research showed that there are 19 utterances of idiomatic expressions found in The Shawshank Redemption movie based on Seidl and McMordie’s (1988). All of 19 idiomatic expressions are classified based on Baker’s (1992) translation strategies into 4 idioms of similar meaning and form, none of idioms of similar meaning but dissimilar form, 10 translations by omission, and 5 translations by omission.